Review of the Role of PPAR Gamma and Agonists in the Development of Heart - Peymani, Maryam; Ghaedi, Kamran; Nasr-Esfahani, Mohammad Hossein (The International Journal of Biotechnology, 2015)
Peroxisome-proliferator activator receptor γ (PPARγ) is a nuclear receptor of central importance in metabolic processes. Recent experimental pieces of evidence demonstrate that PPARγ is implicated in cardiac function and development. Here we reviewed the role of PPARγ and ligands that emerged as a potential new therapeutic target for several cardiac diseases.